2018
DOI: 10.1107/s2053229618016030
|View full text |Cite
|
Sign up to set email alerts
|

Low-dimensional bismuth(III) iodide hybrid material with high activity for the fast removal of rhodamine B

Abstract: Organic–inorganic hybrid lead-based perovskite crystal materials have been widely studied due to their excellent optical–electronic properties. However, the toxicity of lead limits their widespread use. Here, a lead-free perovskite-type compound, tetrakis(1,2,3-trimethylimidazolium) di-μ3-iodido-tetra-μ2-iodido-decaiodidotetrabismuth(III), (C6H11N2)4[Bi4I16], has been successfully synthesized by a simple solvothermal method. It exhibits a zero-dimensional (0D) tetrameric structure, including edge-sharing [Bi4I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…Structures built of finite building blocks are incorrectly referred to as 'zero dimensional'. For example, Chen et al (2018) have reported a leadfree hybrid perovskite containing 'zero-dimensional discrete anionic clusters'. A cluster of atoms is obviously three dimensional but zero periodic, i.e.…”
Section: Dimensionality Versus Periodicitymentioning
confidence: 99%
“…Structures built of finite building blocks are incorrectly referred to as 'zero dimensional'. For example, Chen et al (2018) have reported a leadfree hybrid perovskite containing 'zero-dimensional discrete anionic clusters'. A cluster of atoms is obviously three dimensional but zero periodic, i.e.…”
Section: Dimensionality Versus Periodicitymentioning
confidence: 99%
“…It can be described as two sets of edge-sharing [Bi2I10] 4− bioctahedra, which are linked through four µ2-I and µ3-I bridges. The α-[Bi4I16] 4− architectures are very common in the literature [15][16][17], and they also appear for chloride [18] and bromide [19] bismuthates. The second isomer of the {Bi4I16} anionic family is β-[Bi4I16] 4− B.…”
Section: Introductionmentioning
confidence: 99%
“…As highlighted in C, the rarest isomer γ-[Bi4Br16] 4− can be described as a result of the fusion of two binuclear [Bi2Br9] 3− moieties in which two µ2bridging bromide ligands are converted to µ3 ones. [16,20,22].…”
Section: Introductionmentioning
confidence: 99%